Early Invasive versus Conservative Strategies in Cardiogenic Shock: A Meta-Analysis - Ni Made Dharma Laksmi (Archives of The Medicine and Case Reports, 2025)
Cardiogenic shock (CS) carries a high mortality rate. While early invasive strategies (EIS) like percutaneous coronary intervention (PCI) are often advocated, their superiority over conservative strategies (CS) remains debated. This meta-analysis compared the efficacy and safety of EIS versus CS in patients with CS. A systematic search of PubMed, Embase, and the Cochrane Library was conducted from January 2013 to December 2024. Randomized controlled trials (RCTs) and observational studies comparing EIS (early PCI, mechanical circulatory support) with CS (initial medical therapy) in adult CS patients were included. The primary outcome was all-cause mortality at 30 days. Secondary outcomes included in-hospital mortality, stroke, major bleeding, and acute kidney injury. A random-effects model was used to pool data. Nine studies (n=4,875 patients) were included. EIS was associated with a significantly lower risk of 30-day mortality compared to CS (risk ratio [RR] 0.78; 95% confidence interval [CI] 0.65-0.93; p=0.006). Similarly, EIS reduced in-hospital mortality (RR 0.72; 95% CI 0.61-0.85; p=0.001). There was no significant difference in the incidence of stroke or major bleeding between the two groups. However, EIS was associated with a higher risk of acute kidney injury (RR 1.20; 95% CI 1.05-1.37; p=0.008). In conclusion, in patients with CS, EIS was associated with significantly lower 30-day and in-hospital mortality compared to CS. However, EIS may increase the risk of acute kidney injury. Further research is needed to identify specific patient subgroups that may benefit most from EIS.